SISTEM PEMIDANAAN LEMBAGA PEMASYARAKATAN KLAS IIB KABUPATEN TUBAN DIHIBUNGKAN DENGAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Hariyo Sulistiyantoro (Syiar Hukum, 2011)
A correctional institution is concerned with improving the behavior of criminals, usually by punishing them. It has a very important role in the  effort to restore the prisoners into society. As part of the correctional institution program, coaching is designed to correct the behavior of criminals in order to prevent them from committing a crime again. More importantly, coaching is not intended to make them suffering, and to abandon their human rights. The aim of this article is to give a brief overview of the correctional institution criminal system  in Penitentiary Class IIB of Tuban District under Law No.12 of 1995 on Penitentiary . In general, there are two approaches in conducting  coaching pattern  used by this Correctional Institution, namely by providing general coaching such as religious teaching, civic duties, intellectual capacity building and the raising of legal awareness. The Institution  also provides technical coaching  like  self-reliance building that is  realized by providing various skills that are tailored to the needs of the  prisoners. It should be pointed out, however, that these prisoner rights  are retained subject to  requirements set out in  the existing laws and  regulation. The author concludes that although the provisions of  Law No.12 of 1995 on Penitentiary are adequate to deal with the matters, Ministry of Justice and Human Rights should conduct a monitoring  task in the law enforcement .  Action can be taken to address the incompletenss of the current  legislation on penitentiary.